Midazolam as an induction agent in comparison with propofol as a safe and effective alternative - Singh, J (Journal of Institute of Medicine Nepal, 2013)
Introduction: Propofol produce rapid and smooth induction of anesthesia, with rapid metabolism, which would allow it to be used for the maintenance of anesthesia and free from the risk of anaphylactic reactions. Midazolam a new short acting water soluble Benzodiazepine with cardio vascular effects similar to that of diazepam may be an effective alternative for induction of anesthesia. Methods: In this randomized study, all together 48 patients undergoing various surgical procedures belonging to Orthopedic, General Surgery and Gynecological Surgeries constituted the study group. Group-I (Midazolam Group) received intra-venous Midazolam 0.15mg/Kg for induction of anesthesia and Group-II (Propofol Group) received 2mg/kg intravenous Propofol for Induction of Anesthesia. Induction time, Heart Rate, Non invasive blood Pressure is recorded at 1minute interval for 5 minutes and after that at an interval for 5 minutes for another 30 minutes. Demographic data was analyzed by Student’s t-test. Results: The study showed no statistical significance in hemodynamic responses with either Midazolam or Propofol as an induction agent for General Anesthesia but there was statistically difference with respect to heart rate (P=0.001). Conclusion: Midazolam was proven effective compared to Propofol as an induction Agent. DOI: http://dx.doi.org/10.3126/joim.v34i1.9119 Journal of Institute of Medicine, April, 2012; 34:1 25-32